The Tampa Scale of Kinesiophobia: A Systematic Review of Its Psychometric Properties in People With Musculoskeletal Pain - Dupuis, Frederique; Cherif, Amira; Batcho, Charles; Massé-Alarie, Hugo; Roy, Jean-Sébastien (The Clinical Journal of Pain, 2023)
Objective: The aims of this systematic review were to identify the different versions of the Tampa Scale of kinesiophobia (TSK) and to report on the psychometric evidence relating to these different versions for people experiencing musculoskeletal pain. Methods: Medline [Ovid] CINAHL and Embase databases were searched for publications reporting on the psychometric properties of the TSK in populations with musculoskeletal pain. Risks of bias were evaluated using the COSMIN risk of the bias assessment tool. Results: Forty-one studies were included, mainly with a low risk of bias. Five versions of the TSK were identified: TSK-17, TSK-13, TSK-11, TSK-4, and TSK-TMD (for temporomandibular disorders). Most TSK versions showed good to excellent test-retest reliability (intraclass coefficient correlation 0.77 to 0.99) and good internal consistency (ɑ=0.68 to 0.91), except for the TSK-4 as its reliability has yet to be defined. The minimal detectable change was lower for the TSK-17 (11% to 13% of total score) and the TSK-13 (8% of total score) compared with the TSK-11 (16% of total score). Most TSK versions showed good construct validity, although TSK-11 validity was inconsistent between studies. Finally, the TSK-17, -13, and -11 were highly responsive to change, while responsiveness has yet to be defined for the TSK-4 and TSK-TMD. Discussion: Clinical guidelines now recommend that clinicians identify the presence of kinesiophobia among patients as it may contribute to persistent pain and disability. The TSK is a self-report questionnaire widely used, but 5 different versions exist. Based on these results, the use of TSK-13 and TSK-17 is encouraged as they are valid, reliable, and responsive.
Keywords: Musculoskeletal pain; Reliability; Responsiveness; Tampa Scale of Kinesiophobia; Validity